PENGARUH GREEN HUMAN RESOURCES MANAGEMENT DAN EMPLOYEE ECO FRIENDLY BEHAVIOR TERHADAP KEBERLANJUTAN ORGANISASI YANG DIMEDIASI OLEH KINERJA LINGKUNGAN PADA PERUSAHAAN PDAM SURAKARTA - Ravisa Viningka Selsa Gitaya; Jati Waskito (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the effect of Green Human Resources Management and Employee Eco Friendly Behavior on Organizational Sustainability mediated by Environmental Performance in PDAM Surakarta company. This research method is quantitative. This study used primary data. The method of data collection through surveys using questionnaires that will be given to respondents. The population in this study is employees of the Surakarta Regional Drinking Water Company. The sampling technique in this study is Propotional random sampling. The population of this study was employees who worked in the drinking water company of Surakarta City. The sample size of this study was 75 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. Based on the results and discussion, it was found that Green human resources management has a positive and significant effect on environmental performance. Employee eco friendly behavior has a positive effect and there is significance on environmental performance. Green human resource management has a positive but not significant effect on organizational sustainability. Employee eco-friendly behavior has a positive but not significant effect on organizational sustainability. The results of mediation show that environmental performance cannot mediate between Green human resource management variables to organizational sustainability. The results of mediation show that environmental performance cannot mediate between the variables of employee eco friendly behavior to organizational sustainability